Majorities and Minarets: Religious Freedom and Public Space. Issue 2 (5th June 2014) - Miller, David
Abstract : The problem raised when democratic majorities take decisions that impose restrictions on religious minorities may be avoided through 'the strategy of privatization', but not when the issue is the character of public space. This article considers a challenging case: the Swiss referendum decision to ban any future construction of Islamic minarets. It examines two grounds for opposition: the human right to freedom of religion, and the liberal principle of equal treatment of cultures. It argues that the human right is too limited, and that the equal treatment principle can be trumped by considerations of national identity when public space is involved. Nevertheless, the content of that identity and its public expression must remain open to democratic deliberation, and the Swiss decision can be faulted on those grounds.